The Relationship between Nanocluster Precipitation and Thermal Conductivity in Si/Ge Amorphous Multilayer Films: Effects of Cu Addition. (27th March 2016) - Mohd Tamidi, Ahmad Ehsan; Sasajima, Yasushi
Abstract : We have used a molecular dynamics technique to simulate the relationship between nanocluster precipitation and thermal conductivity in Si/Ge amorphous multilayer films, with and without Cu addition. In the study, the Green-Kubo equation was used to calculate thermal conductivity in these materials. Five specimens were prepared: Si/Ge layers, Si/(Ge + Cu) layers, (Si + Cu)/(Ge + Cu) layers, Si/Cu/Ge/Cu layers, and Si/Cu/Ge layers. The number of precipitated nanoclusters in these specimens, which is defined as the number of four-coordinate atoms, was counted along the lateral direction of the specimens. The observed results of precipitate formation were considered in relation to the thermal conductivity results. Enhancement of precipitation of nanoclusters by Cu addition, that is, densification of four-coordinate atoms, can prevent the increment of thermal conductivity. Cu dopant increases the thermal conductivity of these materials. Combining these two points, we concluded that Si/Cu/Ge is the best structure to improve the conversion efficiency of the Si/Ge amorphous multilayer films.